Video self-reflection and coach development in New Zealand - Mead, S.; Spencer, K.; Kidman, L. (Asia Pacific Journal of Sport and Social Science, 2016)
Drawing on data from semi-structured interviews with New Zealand coaches (N = 6), this study examined how video self-reflection (VSR) was perceived as a tool for learning within `on-going` coach development. This study also looked to determine the potential barriers experienced by coaches before engaging in VSR. Each participant was a performance coach (as identified by the NZ coach development framework (CDF)) with 5+ years coaching experience and had recently (in the previous 12 months) participated in a coach development program that aligned with Sport NZ`s CDF. Five main themes emerged from the data; coaches had a positive perception of the benefits of VSR, a desire to engage in VSR but did not prioritise the time, logistical concerns, a fear of self-confrontation and evidence of knowledge for `modern` coaching development. Findings indicated that coaches valued VSR as a tool for learning; however, the lack of exposure and experience in the process meant coaches did not value the practise enough to dedicate specific time towards it. This study provides an evidence-base that can be used to support National Governing Bodies coach development frameworks, and the modification of content to encourage the use of VSR as a tool for learning.